ON THE OVARIAN EGGS OF BENTHOSEMA FIBULATUM AND B. PTEROTUM (MYCTOPHIDAE) FROM NORTHERN ARABIAN SEA - Hussain, S M; Khan, J Ali (Indian Journal of Fisheries, 2011)
Reports on the fish assessment in theArabian sea (Anon., 1975; 1976; 1977) indicateabundant myctophid catches (upto amaximum 20,000 kg per hour of trawling).The abundant myctophid species belongedto genus Benthosema, of which two speciesB. fibulatum and J?. pterotum are dominant.The eggs and larvae of the two species wereabundant among oceanic plankton in December,1964-April, 1965 (Nellen, 1973).